Creating and facilitating change for Person‐Centred Coordinated Care (P3C): The development of the Organisational Change Tool (P3C‐OCT). (15th November 2017) - Horrell, Jane; Lloyd, Helen; Sugavanam, Thavapriya; Close, James; Byng, Richard
Abstract: Background: Person Centred Coordinated Care (P3C) is a UK priority for patients, carers, professionals, commissioners and policy makers. Services are developing a range of approaches to deliver this care with a lack of tools to guide implementation. Methodology: A scoping review and critical examination of current policy, key literature and NHS guidelines, together with stakeholder involvement led to the identification of domains, subdomains and component activities (processes and behaviours) required to deliver P3C. These were validated through codesign with stakeholders via a series of workshops and cognitive interviews. Results: Six core domains of P3C were identified as follows: (i) my goals, (ii) care planning, (iii) transitions, (iv) decision making (v), information and communication and (vi) organizational support activities. These were populated by 29 core subdomains (question items). A number of response codes (components) to each question provide examples of the processes and activities that can be actioned to achieve each core subdomain of P3C. Conclusion: The P3C‐OCT provides a coherent approach to monitoring progress and supporting practice development towards P3C. It can be used to generate a shared understanding of the core domains of P3C at a service delivery level, and support reorganization of care for those with complex needs. The tool can reliably detect change over time, as demonstrated in a sample of 40 UK general practices. It is currently being used in four UK evaluations of new models of care and being further developed as a training tool for the delivery of P3C.